GRANULAR PARAKERATOSIS: REPORT OF 2 ECUADORIAN CASES AND REVIEW OF THE LITERATURE - Verónica Uraga; Andrea Lubkov; Annette Morán; Juan Carlos Garcés; Enrique Uraga (Our Dermatology Online, 2013)
Granular Parakeratosis is a rare disorder of keratinization usually presented in adults. There are only fews reports in children. We present two cases, one in an adult and the other in a 7-month-old infant.